Pengaruh Level Campuran Tepung Daun Kelor-Lamtoro dalam Media Dasar Terhadap Pemanfaatan dan Konversi Nutrisi Maggot Lalat Tentara Hitam (Hermetia illucens) - Rendemai, Isidorus; Dami Dato, Twen O.; Benu, Imanuel; Oematan, Gustaf (Animal Agricultura, 2024)
leaf meal mixture in the basal medium on the utilization of dry matter, crude protein, crude fat, and nutrient conversion in black soldier fly larvae (BSFL). The experiment was designed using a completely randomized design (CRD) with five treatments (0%, 10%, 20%, 30%, and 40% of the Moringa-Leucaena leaf meal mixture) and four replications. The basal medium consisted of 80% rice bran and 20% cornmeal, fermented for seven days before use. A total of 1000 BSFL were introduced into the fermented medium in each experimental unit, and harvesting was conducted on day 14.The results showed that the addition of the Moringa-Leucaena leaf meal mixture significantly increased dry matter utilization (DMU: 0.17–0.33%), crude protein utilization (CPU: 1.21–1.62%), and crude fat utilization (CFU: 4.00–7.00%), while reducing the feed conversion ratio (FCR: 6.23–3.27). The optimal level for all variables was found in the treatment with 40% Moringa-Leucaena leaf meal mixture. In conclusion, the addition of Moringa-Leucaena leaf meal as a protein source in the basal medium can improve nutrient utilization and feed efficiency in black soldier fly larvae.